The optimization of water network model in the central of Demak District - Rezagama, Arya; Sutrisno, Endro; Susilo, Joko; Tommy, Ervando; Lovely, Nosa Ajulva (Sustinere: Journal of Environment and Sustainability, 2018)
Demak Waterwork Company (DWC) has served 21,178 customers with the capacity flow of 159.33 l/s. The capacity was predicted to reach 300 l/s or double in in 2027. The Water Distribution Networks (WDN) was developed in a large zonation, but the water supply to the customer was not well managed. Low pressure especially at peak hours, the level of leakage, and the difficulty to detect leakage are water supply problems should be solved by WDN. The objectives of this study are forecasting the demand for drinking water in the 2036 and designing a zoning system to meet future needs of drinking water. This study applied Epanet Modelling to simulate the water network system in existing and predicted condition. The result show that the characteristics of pipes, pipe materials and pipe size based on the load of drinking water should be considered for pipe replacement. Some developmental strategies e.g. improving the capacity, establishing zones, and resizing the pump capacity improve the reliability and efficiency of the water distribution network. The pressure model resulted in sufficient value to supply the whole area of more than 0.5 bar in service pipe.